The Role of Calcium in Inflammation-Associated Bone Resorption - Klein, Gordon L. (Biomolecules, 2018)
The aim of this mini-review is to discuss the role of calcium in the process of cytokine-mediated bone resorption in an effort to understand the role circulating calcium may play in the resorption of bone. The liberation of calcium and possibly phosphorus and magnesium by bone resorption may sustain and intensify the inflammatory response. We used a burn injury setting in humans and a burn injury model in animals in order to examine the effects on the bone of the systemic inflammatory response and identified the parathyroid calcium-sensing receptor as the mediator of increasing bone resorption, hence higher interleukin (IL)-1 production, and decreasing bone resorption, hence the lowering of circulating ionized calcium concentration. Thus, extracellular calcium, by means of the parathyroid calcium-sensing receptor, is able to modulate inflammation-mediated resorption.